Synergistic Effect of Supplementation of Coated Sodium Butyrate and Bacillus Subtilis on Cost Effectivenessin Broiler Chicken Production - C.Mekala; S. Senthil Kumar; P.Vasanthakumar; M. Moorthy; A.Natarajan; G.Gomathi (Indian Journal of Animal Nutrition, 2024)
The present experiment was carried out to assess the synergistic efficiency of supplementation of coated sodium butyrate and Bacillus subtilis as a substitute for antibiotic growth promoter in broiler diet and to work out the cost effectiveness of broiler chicken production. A biological trial was carried out with 216 day–old cobb 400 broiler chicks distributed to six experimental groups with six replicates, each replicate containing six chicks. The experimental groups were fed with basal diet (T1), a basal diet with antibiotic (T2), probiotic (Bacillus subtilis) alone (100 g/ton of diet) (T3), and coated sodium butyrate high at 0.18 (T4) or medium 0.09 (T5) and low 0.045 (T6) per cent levels combined with Bacillus subtilis (100 g/ton of diet). The coated sodium butyrate (CSB) was used as lipid encapsulated sodium butyrate. A commercial probiotic supplement of Bacillus subtilis with 1x 1012 cfu/g was used for this experiment. The trial was conducted in a deep litter pen and last for 35 days. The increase in the revenue of Rs. 4.31 and Rs. 1.61 per kg live weight gain in the group supplemented with CSB at 0.09 per cent and Bacillus subtilis 100 g/ton of diet (T5) as compared to basal diet and antibiotic group (T2), respectively. Therefore, it is recommended to include the CSB at 0.09 per cent and Bacillus Subtilis at 100 g/ton of feed as an alternate for antibiotics in the broiler diet.